Who needs classical music?: Cultural choice and musical value. - Johnson, Julian (Oxford Oxford university press, 2002)
During the last few decades, most cultural critics have come to agree that the division between "high" and "low" art is an artificial one, that Beethoven's Ninth and "Blue Suede Shoes" are equally valuable as cultural texts. In Who Needs Classical Music?, Julian Johnson challenges these assumptions about the relativism of cultural judgements. The author maintains that music is more than just "a matter of taste": while some music provides entertainment, or serves as background noise, other music claims to function as art. This book considers the value of classical music in contemporary society, arguing that it remains distinctive because it works in quite different ways to most of the other music that surrounds us.This intellectually sophisticated yet accessible book offers a new and balanced defense of the specific values of classical music in contemporary culture. Who Needs Classical Music? will stimulate readers to reflect on their own investment (or lack of it) in music and art of all kinds.